Human capital and child protection: A research framework in the CRC context. (September 2021) - Wulczyn, Fred; Parolini, Arno; Huhr, Scott
Abstract: Since it was adopted November 1989, the Convention on the Rights of the Child has shaped the objectives for child protection systems around the world. Generally, those objectives fall along three dimensions: permanency, safety, and well-being. However, despite well-being receiving increasing attention in light of evidence that points to the importance of early childhood experiences on life course outcomes, child protection systems have so far struggled to find clear definition of well-being as a developmental construct. In this article, we propose a definition of child well-being that draws on the economic literature pertaining to skill formation and human capital. We argue that human capital, as a multidimensional concept that incorporates cognitive skills, non-cognitive skills, and health, should be added to the list of considerations policy makers contemplate when their attention turns to well-being provided there is research evidence for doing so. To that end, we discuss the several advantages the human capital framework offers within a child protection context. We then describe a theoretical framework and analytical approach to the study of skill formation. We are particularly interested in dynamic models wherein the skills one has influence the rate at which new skills are acquired, with specific emphasis on risk and protective factors across the life course of childhood. Overall, our discussion highlights how a dynamic model of human capital formation aligns with Convention on the Rights of the Child and notions that children in child protection systems have a right to develop the abilities they will need to be responsible adults.